2010
DOI: 10.1093/rheumatology/keq205
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of anti-cyclic citrullinated peptide antibody and rheumatoid factor to detect rheumatoid arthritis in patients with systemic sclerosis

Abstract: The serum titre of anti-CCP Ab is higher in SSc-RA overlap patients than in SSc patients with or without arthralgia. The finding of high titres of anti-CCP Abs and the elevated levels combinatory with other RA-related Abs may help to define the diagnosis of SSc-RA overlap. MMP-3 might be a better marker to assess skin involvement rather than joint involvement in SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 13 publications
4
13
0
1
Order By: Relevance
“…These figures appear comparable to previously published studies. Ueda‐Hayakawa et al . reported IgM‐RF positivity in 11% of their cohort with SSc and serum anti‐CCP antibody levels significantly elevated in SSc‐RA overlap patients compared with SSc patients with or without arthralgia ( P < 0.05 and P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These figures appear comparable to previously published studies. Ueda‐Hayakawa et al . reported IgM‐RF positivity in 11% of their cohort with SSc and serum anti‐CCP antibody levels significantly elevated in SSc‐RA overlap patients compared with SSc patients with or without arthralgia ( P < 0.05 and P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 93%
“…Cross‐sectional studies have estimated the point prevalence of anti‐CCP antibodies in patients with SSc from 1% to 15%. The presence of these antibodies may help in the identification of the cases of true SSc‐RA overlap . Studies have shown anti‐CCP titres are reliable markers of SSc‐RA overlap…”
Section: Introductionmentioning
confidence: 99%
“…Erosive polyarthritis (82%), pulmonary fibrosis (77%), esophageal involvement (55%), and cardiac manifestations (50%) are most commonly observed in SSc-RA overlap patients (11). The findings of high anti-CCP antibody titers may help to define the diagnosis of SSc-RA overlap syndrome and facilitate the diagnosis and appropriate treatment: the serum anti-CCP antibody titer is higher in patients with SSc-RA overlap syndrome than in SSc patients with/without arthralgia (12,13). In the present case, SSc-RA overlap syndrome was diagnosed based on the presence of several compatible features.…”
Section: Discussionmentioning
confidence: 99%
“…16 In particular, ACPA has a sensitivity of 50% to 100% and specificity of 95% in identifying patients with SSc-RA overlap syndrome. 16,17 SSc-RA overlap is a distinct genetic, clinical, and serologic entity and is uncommon in SSc, with a prevalence of 1% to 5%. 17 However, these patients are more likely to develop bone erosions and joint deformities.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…16,17 SSc-RA overlap is a distinct genetic, clinical, and serologic entity and is uncommon in SSc, with a prevalence of 1% to 5%. 17 However, these patients are more likely to develop bone erosions and joint deformities.…”
Section: Laboratory Findingsmentioning
confidence: 99%